Incidencia del Somatotipo en el aprendizaje de la técnica Bandal Chagui. Liga Cantonal de Pallatanga 2019 - Luis Fernando, Silva Rodríguez (2020)
This project aims to determine the incidence of somatotype in the learning of the Banda Chagui technique. The study was carried out in the Pallatanga Cantonal Sport League 2019 using specific kick methodologies, verifying that somatotype assimilated the technique satisfactorily. Clarifying that the somatotype is a classification of form and bases on the concepts of experiences of each situation. The methodology used for the execution of the research, according to the level was exploratory, of field design. The population was 87 athletes from the Pallatanga Cantonal Sports League, where the sample was 28 boys and girls between 8 and 11 year old. The technique used was the observation, and the instruments for the independent variable the I.M.C was used, an observation sheet was used as an instrument. When analyzing the relationship between the two variables, it was determined that there is no significance between them. Other factors may be involved in the learning of the technique.